Late outcome of right ventricular outflow tract repair using bicuspid pulmonary prosthesis in tetralogy of Fallot surgery repair: case report - Maluf,Miguel Angel (2009)
We present a case of a 19 year-old female patient, with tetralogy of Fallot and hypoplastic pulmonary ring. Diagnosis was performed by echocardiography and cardiac catheterization. The surgical repair was performed at the age of 2 years old. A right ventricular outflow tract remodeling was performed using a porcine pulmonary bicuspid prosthesis. The patient presented a uneventful follow-up during 17 years. Postoperative assessment has shown: mild pulmonary insufficiency and mild pulmonary ventricle gradient, satisfactory right ventricular performance and prosthesis not presenting calcification. This is an option to correct the tetralogy of Fallot adopted by our Institution in the last two decades.